Isospecific alternating copolymerization of unprotected polar styrenes and ethylene by the Cs symmetric scandium precursor via synergistic effects of two substituent groups. (August 2021) - Wang, Tiantian; Wu, Chunji; Wang, Baoli; Cui, Dongmei
Highlights: The highly syndioselective/isoselective coordination polymerization of polar monomers bearing two functional groups has been achieved by rare-earth metal complexes. The unique synergistic effects of two polar groups are found, for the first time, in the copolymerizations of ethylene and polar styrenes. This work represents the first example of perfectly isoselective alternating copolymerization of ethylene and the unprotected polar styrenes. Abstract: Coordination polymerization of polar monomers bearing two functional groups has been a formidable challenge due to much higher poisonous possibility. In this contribution, we reported the coordination (co)polymerization of FMOSs bearing two functional groups, 4-fluoro-2-methoxystyrene (2, 4-FMOS), 5-fluoro-2-methoxystyrene (2, 5-FMOS) and 6-fluoro-2-methoxystyrene (2, 6-FMOS) using the quinolyl methylene fluorenyl complexes (Flu-CH2 -Qu) Sc (CH2 SiMe3 )2 (1 ) and (Flu-CH2 -Qu)Y(CH2 SiMe3 )2 (THF) (2 ) and the β -diketiminato complex (bis(2, 6-dimethyl anilido)ketimine)Y(CH2 SiMe3 )2 (THF) (3 ). Excellent syndiotactic P(2, 6-FMOS) ( rrrr > 99%) was isolated from complex 1 in a moderate activity, while, almost atactic P(2, 6-FMOS) was obtained by complexes 2 and 3 . Polymerizations of both 2, 4-FMOS and 2, 5-FMOS showed high activities and excellent syndioselectivity ( rrrr >99%) by complexes 1 and 2, and perfect isoselectivity ( mmmm > 99%) by complex 3 . Moreover, copolymerizations of ethylene (E)/2, 4-FMOS and E/2, 6-FMOS catalyzed by complex 1, respectively, displayed the positive comonomer effect in much higher activities than those of E/2, 5-FMOS and E/2-methoxystyrene (MOS) to afford perfect isotactic ( mmmm > 99%) alternating products E- alt -FMOS. This work represents the first example of isoselective alternating copolymerization of E and the unprotected polar styrenes, in particular those bearing two polar substituents. The reasons for the formation of isoselective and alternating structures of polymers might be attributed to the unique synergistic effects of fluorine and o -methoxy groups. The mechanism was elucidated by the DFT calculations. Graphical abstract: Image, graphical abstract